Vibrational Spectra of the thioglycolate complexes of Zn(II) and Cd(II), structure and natural bond orbitals (Research, Society and Development, 2023)
The objective of this research was to characterize the vibrational spectrum of the Zn(II) and Cd(II) thioglycolate complexes, as well as their structures, vibrational analysis and the natural orbitals of bonds, through the infrared spectrum with Fourier transform (FT -IR) and Raman. The thioglycolate complexes of Zn(II) and Cd(II) were synthesized following  procedures given by  the graphical method, and structural analysis was performed  through  a theoretical-experimental method  using both, the hybrid RHF/MP2:STO-3G and the experimental FT-IR and FT-Raman spectra. Calculations were performed on the optimized structure and harmonic vibrational wavenumbers for both complexes were obtained. Second derivative of the vibrational spectra and deconvolution analysis were also performed. The infrared and Raman spectra show many combination and overtone bands in both cases. Calculated and experimental spectra confirmed the structural hypothesis considering two ATG (thioglycolic acid) with two water molecules in the coordination sphere of the central atoms. The natural bond orbital analysis (NBO) was also carried out to study the Zn(II) and Cd(II) hybridization leading to a pseudo-octahedral geometry for both complexes.